A Formal Enantioselective Synthesis of (–)-Epiquinamide by Proline-Catalyzed One-Pot Sequential α-Amination/Propargylation of Aldehyde and Asymmetric Dihydroxylation of Olefin - Ahuja, Brij Bhushan; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Synlett, 2016)
Two independent routes to the formal synthesis of (–)-epiquinamide, have been described: the first route utilizes an l-proline-catalyzed one-pot sequential α-amination/propargylation of aldehyde, while the second one employs asymmetric dihydroxylation as the key reaction to install the stereochemistry. While the first synthesis was accomplished in nine steps with 24.4% overall yield and dr 9:1, the second strategy resulted in the synthesis in eight steps with 36.4% overall yield and with perfect enantiocontrol.
Keywords: amination; dihydroxylation; diastereoselective; proline; quinolizidine